Experimental Investigation of the Effect of the Cross-Sectional Geometry on the Flow - Gul, Hasan; Evin, Duygu (Gazi Univ, 2007)
In this study, flow and friction characteristics in the rectangular-to-rectangular transition channels, which have cone angles of phi = 4(0),5(0),6(0) were investigated experimentally. The ratio of the channel inlet cross-sectional area to that of exit is 1:2. The transition ducts have different geometrical dimensions and cone angles. The duct entry and exit aspect ratios were chosen as 1.42 and 1.4, respectively. Measurements were taken at several stations, x/L, with the Reynolds number ranging from 2x10(5) to 5x10(5). Velocity profiles were measured starting from inlet to downstream using hot-wire anemometer. Based on experimental results, different flow characteristics were obtained. Friction coefficient decreased with increasing pipe length and increasing Reynolds number. It was seen that cross flows occurred at low Reynolds numbers.
Keywords: Asymmetric transition duct; Secondary Flow; Flow measurement